EFFECT OF GROWTH CONDITIONS ON THE BIREFRINGENCE OF MIXED CRYSTALS REVEALED IN ALUM SOLID SOLUTIONS - Shtukenberg A.G.; Punin Yu.O.; Soloviev V.N. (My University, 2000)
An experimental study of optical anomalies in solid solutions of alums in relation to their composition, growth temperatures and rates, and hydrodynamic regime was carried out. Theoretical analysis of the data showed that they can be understood in terms of a mechanism of kinetic ordering of the isomorphous atoms (the phenomenon of so-called 'growth dissymmetrization'). A theoretical model is presented which is supported by data for a number of minerals and synthetic compounds, which are known for their optical anomalies due to growth dissymmetrization.